Evaluation of risk factors and effective factors in determining the prognosis of ovarian cancer: Risk factors and prognosis of ovarian cancer - Liu, Chenxi; Su, Hongling (Cellular and Molecular Biology, 2022)
Ovarian cancer is still one of the leading causes of death from reproductive system cancers. Despite recent advances in treating this cancer, ovarian cancer is the fourth cause of death in women. Knowing the risk factors of ovarian cancer and the factors affecting the prognosis of this tumor can be helpful. This study investigates risk factors and practical factors in determining the prognosis of ovarian cancer. In the present study, we searched through various databases such as Wiley Online Library, Google Scholar, PubMed, and Elsevier with the keywords Polycystic Ovarian, Ovarian Estrogen-Dependent Tumors Syndrome Chronic Inflammation, Prognosis of Ovarian Cancer, among published articles from 1996 to 2022. Based on these studies, we investigated the age of menstruation, age of menopause, number of pregnancies, family history of ovarian cancer and genital tract cancer, use of birth control pills, histological type of tumor, degree of cell differentiation, type of surgery, and post-surgery treatments, and examination of the serum level of tumor marker CA12, as well as the role of polycystic ovary syndrome in the development of ovarian cancer. In general, infertility was one of the most important risk factors and the serum level of tumor marker CA125 was one of the most important determinants of ovarian cancer prognosis.